IMPLEMENTASI ALGORITMA SCHMIDT-SAMOA PADA ENKRIPSI DEKRIPSI EMAIL BERBASIS ANDROID - Willy Ristanto; Willy Sudiarto Raharjo; Antonius Rachmat Chrismanto (Universitas Kristen Duta Wacana, 2013)
Cryptography is a technique for sending secret messages. This research builds an Android-based email client application which implement cryptography with Schmidt-Samoa algorithm, which is classified as a public key cryptography. The algorithm performs encryption and decryption based on exponential and modulus operation on text messages. The application use 512 and 1024 bit keys. Performance measurements is done using text messages with character number variation of 5 – 10.000 characters to obtain the time used for encryption and decryption process. As a result of this research, 99,074% data show that decryption process is faster than encryption process. In 512 bit keys, the system can perform encryption process in 520 - 18.256 miliseconds, and decryption process in 487 - 5.688 miliseconds. In 1024 bit keys, system can perform encryption process in 5626 – 52,142 miliseconds (7.388 times slower than 512 bit keys) and decryption process with time 5463 – 15,808 miliseconds or 8.290 times slower than 512 bit keys.